An analysis of the strategies employed by the opposition political parties in an attempt to consolidate power in Zimbabwe: The case of MDC since 2000-2016. - Nduku, Kudzai L. (Midlands State University, 2020)
The research analyzed the strategies employed by the opposition political parties in an attempt to consolidate power in Zimbabwe; the case of MDC since 2000- 2016. For the past 16years MDC has been engulfed in a power battle with the current power party ZANU-PF .however it can be noted that MDC is not the only opposing party that has been battling to consolidate power in Zimbabwe. There have been other political parties that have emerged and more are still rising to the accasion.All the parties have been silently thwarted and booted out of the political battlefield looking at the Tekere party ZUM and Simba s party. The research delved into the problems militating against these opposition political parties that facilitate their decisive failures. The research looked at the strategies that have been implemented by MDC and other opposition political parties and why these strategies have repeatedly failed. Data was collected using interviews, questionnaires, focus groups and documents. The data was quantitatively and qualitatively analyzed through the use of thematic and content analysis. Tables and graphs were used to present the statistical data. The findings revealed that MDC and other opposition political parties lack foresight from birth as they fight the wrong battles, the do not plan their election strategies on time, they do not have the right strategies ,tools and weapons to win an election and could possibly use a change with the consulting team. MDC has been playing the victim card and needs to abandon being on the defensive and start attacking by using ZANU-PF s strategies, after all politics is a dirty game. The findings also reviewed that the MDC has less influence in the rural areas where 70% of the population of Zimbabwe resides. In order to ameliorate the challenges being faced by the MDC and other opposition political parties the researcher proffered recommendations that could possibly help rectify the problems .the recommendations included the need to set polling dates that cater for all its targeted audience, possibly expanding the audience looking at prisoners and probably altering the voting age ,designing logos that capture the attention of voters ,changing their means of communication as to be able to communicate with even those that are disabled and illiterate and having a tactful and strategic campaigning team.